Total synthesis of (−)-isatisine A via a biomimetic benzilic acid rearrangement. Issue 22 (3rd June 2015) - Xiao, Mingxing; Wu, Wei; Wei, Lin; Jin, Xiaojie; Yao, Xiaojun; Xie, Zhixiang
Abstract: The biomimetic total synthesis of potential anti-HIV (−)-isatisine A, a novel alkaloid with an unprecedented fused tetracyclic skeleton, was accomplished in eight steps from indole and known 4, 6- O -isopropylidene-protected glucal. The synthetic strategy was inspired primarily by the proposed biogenetic hypothesis that indole C -furanoside would be derived from indole C -glucoside via a ring contractive benzilic acid rearrangement. The biogenetic hypothesis was enabled by model studies: the O -glucoside was converted to O -furanoside via a benzilic acid rearrangement. Graphical abstract: